ANALISIS VARIABILITAS SPASIAL DAN TEMPORAL CURAH HUJAN DI WILAYAH GUNUNG MERAPI - Dewi Ayu Sofia; Joko Sujono; Djoko Legono (TEKNISIA, 2018)
Rainfall intensity is one of the main trigger factors of cold lava flow on the active volcano slope, such as Mount Merapi. In the event of cold lava flood, where the rainfall as the trigger, there is a process of transformation of rainfall into the flow. Therefore, it is necessary to analyze the characteristics of rainfall, such as variability in terms of space (spatial) and time (temporal). This is important because of Indonesia is passed by the equator, so the rainfall variability is very high. This paper will analyze the spatial and temporal variability of rainfall in the area of Mount Merapi. Rainfall spatial variability was mapped based on the results of interpolation of the maximum rainfall data by Inverse Distance Weight (IDW) method, while the temporal variability was analyzed based on the average rainfall data distribution or maximum annual rainfall of each duration by unisolated event method. The results showed that the average rainfall or maximum rainfall for duration of 1 hour - 8 hours mostly occurred in the daylight until afternoon, between the hours of 13:00 to 17:00 with the incidence of heavy rain occurred in a short duration that is on the duration of 1 hour, 2 hours , 3 hours and 4 hours. Spatial mapping results show similar pattern of distribution where the maximum rainfall position is located in the west side of Mount Merapi.